Relations between attorney temporal structure and children's response productivity in cases of alleged child sexual abuse - Klemfuss, J. Zoe (Legal and criminological psychology, 2017)
Purpose. Previous research has demonstrated that attorney question format relates to child witness' response productivity. However, little work has examined the extent to which attorneys provide temporal structure in their questions, and the effects of this structure on children's responding. The purpose of this study was to address this gap in the literature to identify methods by which attorneys increase children's response productivity on the stand without risking objections from opposing counsel for ‘calling for narrative answers’. Methods. In this study, we coded criminal court transcripts involving child witnesses (5–18 years) for narrative structure in attorney questions and productivity in children's responses. Half of the transcripts resulted in convictions, half in acquittals, balanced across key variables: child age, allegation severity, the child's relationship to the perpetrator, and the number of allegations. Results. Prosecutors and defence attorneys varied substantially in their questioning tactics. Prosecutors used more temporal structure in their questions and varied their questioning by the age of the child. These variations had implications for children's response productivity. Conclusions. Results indicate that temporal structure is a novel and viable method for enhancing children's production of case-relevant details on the witness stand.